Renewable energies and ecosystem service impacts. (August 2015) - Hastik, Richard; Basso, Stefano; Geitner, Clemens; Haida, Christin; Poljanec, Aleš; Portaccio, Alessia; Vrščaj, Borut; Walzer, Chris
Abstract/Summary: Expansion of renewable energies (=RE) is a key measure in climate change mitigation. For this expansion mountainous areas are regarded as specifically suitable because of their high-energy potential. However, mountains also are biodiversity hot-spots and provide scenic landscapes and therefore offer high natural and cultural value. Preserving this natural and cultural value whilst intensifying RE, is expected to increase land use conflicts. This is of great concern in particular for vulnerable areas such as the Alps. Reconciling RE expansion with the preservation of natural and cultural values and thus minimizing environmental impacts represents one of the most important challenges now. For this a systematic assessment of the wide range of impacts is needed. This literature review scrutinizes RE resources which are relevant in the Alpine region and their effects on the environment by applying the Ecosystem Service approach. Thereby, we identified possible environmental constraints when exploiting Alpine RE potentials and generated recommendations for future strategies on expanding RE. The outcomes highlight the strong need for interdisciplinary research on RE and environmental conflicts. Interdisciplinary approaches such as the concept of Ecosystem Services can help to cover the wide range of aspects associated with these particular human–environment interrelations.